A Mixed PC61BM‐COi8DFIC Based Electron Transport Material for Inverted High‐performance Perovskite Solar Cells. Issue 1 (28th November 2022) - Ali, Jazib; Li, Yu; Song, Jingnan; Zhang, Ming; Zhou, Guanqing; Xu, Jinqiu; Zhu, Lei; Hussain, Ahmad; Khan, Firoz; Liu, Feng
Abstract: This study reports a blend of [6, 6]‐phenyl‐C61‐butyric acid methyl ester (PC61 BM) and CO i 8DFIC non‐fullerene acceptor (NFA) as an electron transport layer (ETL) in perovskite solar cells (PSCs). This mixed small‐molecule ETL showed good inter‐molecule mixing, reduced intermolecular distances and decent morphology, resulting in excellent charge carrier transport properties. Morever, charge carrier extraction and transport at the perovskite/ETL interface was optimized by reducing surface traps and defects due to the passivation ability of various terminal groups from the CO i 8DFIC molecule. A high power conversion efficiency (PCE) of 19.12 % was achieved by taking advantage of benefits from both molecules, showing much better performance than the invidual PC61 BM or CO i 8DFIC (7.13% for using the NFA only). Moreover, the storage and ambient stabilities of the mixed ETL‐based PSCs increased dramatically compared to control devices. Abstract : Introducing fullerene (PC61 B) into a non‐fullerene (CO i 8DFIC) acceptor suppresses its high crystallization nature, showed good inter‐molecule mixing, reduced intermolecular distances and decent morphology, resulting in excellent charge carrier transport properties and benefits from the order phase of fullerene.